2006
DOI: 10.1080/15389580600789127
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Loads and Intervertebral Motions During Whiplash

Abstract: During whiplash, the cervical spine is subjected to not only bending moments, but also axial and shear forces. These combined loads caused both intervertebral rotations and translations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Present peak canal narrowing was smaller (1.8 vs. 3.5 mm) and peak foraminal height and area narrowing were larger (3.9 vs. 1.8 mm; 6.5 vs. 4.5 mm 2 ) than the previously reported data, likely due to differences in neck loads. The headneck model, with its T1 vertebra fixed to a mini-sled which accelerated horizontally, experienced large shear and tensile neck loads [11] likely increasing canal narrowing. These loads are contrasted by large compressive neck loads of the present model due to straightening of the kyphotic thoracic curvature and upward torso ramping [9], which likely increased foraminal height and area narrowing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present peak canal narrowing was smaller (1.8 vs. 3.5 mm) and peak foraminal height and area narrowing were larger (3.9 vs. 1.8 mm; 6.5 vs. 4.5 mm 2 ) than the previously reported data, likely due to differences in neck loads. The headneck model, with its T1 vertebra fixed to a mini-sled which accelerated horizontally, experienced large shear and tensile neck loads [11] likely increasing canal narrowing. These loads are contrasted by large compressive neck loads of the present model due to straightening of the kyphotic thoracic curvature and upward torso ramping [9], which likely increased foraminal height and area narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…Another cadaveric study demonstrated that physiologic extension can decrease the cervical foraminal area by as much as 20% [8]. Rear crashes simulated using osteoligamentous neck specimens have demonstrated nonphysiologic intervertebral extension and posterior translation of the lower cervical spine [9][10][11]. These motions may potentially cause transient neural tissue compression leading to injury and chronic radicular symptoms in whiplash patients.…”
Section: Introductionmentioning
confidence: 99%
“…The same relations involving points B i and B i−1 can be specified simply by replacing A with B in formulae (45) and (46). As can be seen, the equations of motion (43) can be rearranged and presented in the matrix form (1), where (47) and the matrix M consists of the coefficients a i j .…”
Section: Multibody Model Of Cervical Spinementioning
confidence: 99%
“…6, shape representation of every body is based on eight characteristic points. Similar to the models described in [46,47], the center of mass is positioned at the center of the segment connecting the corners P 1 and P 6 of the vertebral body. It is assumed that point P 5 of the ith member and P 2 of the next one are coupled by a link rigidly connected with the lower body, and the pivot O i+1 is located in the point P 2 .…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation